Key Factors Analysis of E-Commerce and Marketplace Purchasing Decision in Palembang - Aslamia Rosa; Iisnawati Iisnawati; Islahuddin Daud (Faculty of Economics, Universitas Sriwijaya, 2018)
We could find the existing of many e-commerce and market place in Palembang, such as MatahariMall.com, Zalora, Lazada, Tokopedia, Blibli, Shopee, Elevania and Bukalapak. To win the competition and build a sustainable competitiveness, those e-commerce and market place need to hold the key factors of online purchase decision. This research purpose is to investigate online shopping experience, word of mouth and web brand image affect to web trustworthiness and whether purchase decision affected by web trustworthiness and online shopping experience. The data taken from questionnaires that distributed to 100 respondents in Palembang. This research analyzed by using Structural Equation Modelling (SEM). The results show a positive influence between online shopping experience and branding image to web trustworthiness. Word of mouth does not have influence to web trustworthiness. The result found that positive influence between web trustworthiness to purchase decision, whereas online shopping experience does not have influence to purchase decision.